Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Café Kozi Coffee Bekasi Selatan - Nurbaiti, Dewi; Rachmawati, Annisa Widya Ayu (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research was conducted at Café Kozi Coffee Bekasi Selatan. Café Kozi Coffee Bekasi Selatan is a culinary café that offers a variety of food and beverage choices from several countries located in south Bekasi. The problem at Café Kozi Coffee Bekasi is facting tight competition amidst the increasing number of coffee shops and consumer preferences. The purpose of the study was to determine and analyze problems, obstacle and solutions to marketing strategies ti increase sales at Café Kozi Coffee Bekasi. Through the STP (Segmenting, Targeting, Positioning) analysis method and this marketing mix shows that Kozi Coffee Bekasi can increase sales and survive in market share by identifying the right market segments, targeting potential customers effectively and positioning products to customers strategically.